Iconography: Sundanese Calligraphy as Artistic Expressions of Identity - Raden, Agung Zainal Muttakin; Rustopo, Rustopo; Haryono, Timbul; Pratama, Dendi (Harmonia: Journal of Arts Research and Education, 2023)
The Sundanese script is one of Indonesia’s traditional scripts. The existence of Sundanese script is still being preserved by cultural activists and the Sundanese script literacy community, one of which is through calligraphy in Sundanese script. This article will analyze the calligraphy of Sundanese script by Edi Dolan posted on his social media. The Sundanese calligraphy that will be discussed is in the form of puppets, animals, and humans. The Sundanese calligraphy will be reviewed through an iconographic approach. Iconography has three levels in analyzing objects, namely (1) Pre-iconography, which is to describe the formal aspects of the object; (2) Iconography, which is to interpret images, stories, and metaphors; (3) Content analysis through revealing the intricacies of the object. The results of the research elaborate on the formal aspects found in Sundanese calligraphy objects, resulting in multidimensional interpretations built on images, stories, and other multidimensional object meanings, thus showing a complete correlation of all these aspects in expressing Sundanese identity.